School Differences in the Predictive Validity of Primary School Examinations among Secondary School Students in Kenya - Agingu, Eunice Atieno (International Journal of Academic Research in Business and Social Sciences, 2017)
The purpose of this study was to determine school category differences in the predictive validity of KCPE among public secondary school students in Kisii central Sub-county, Kenya. The study adopted Correlational and Ex-post-facto research designs. The study population was 3,897 KCSE candidates from 55 public secondary schools. Stratified random sampling based on school type (day and boarding) was used to select 16 public secondary schools for the study. Saturated sampling was employed to include all KCSE candidates, whose KCPE marks were available in each sampled school, yielding a sample of 1,391 students. Data used included 2006 KCPE scores and 2010 KCSE scores of the same students under study. It was analyzed quantitatively using correlations and regression analyses. There was no statistically significant difference in correlation of KCSE and KCPE scores based on school category. The study concluded that KCPE scores is a good predictor of KCSE scores regardless of school category. It recommended that KCPE should continue to be used as selection tool for secondary school admission and that learners should be encouraged to join any type of school convenient to them regardless of whether they are day or boarding schools.
Keywords: Kenya Certificate of Primary Education (KCPE); Kenya Certificate of Secondary Education (KCSE); Predictive Validity; Academic Achievement; School category